Determinação dos níveis de anticorpos séricos e salivares AntiPGL-1 de contatos, com idade inferior a 15 anos, de pacientes diagnosticados com hanseníase no município de Rio Largo, Alagoas - Cunha Júnior, José Evandro (2018)
Leprosy is considered a serious public health problem due to its difficult epidemiological control and the risk of causing major physical disabilities. Investigation of serological markers, such as the anti-PGL-1 antibody, targeting a glycolipid present on the cell wall of the leprosy-causing bacteria, has been of paramount importance in investigating exposure to bacillus and estimating exposure time to same. The aim of the present study was to determine the levels of anti-PGL-1 antibodies, serum and salivary, from intra and peridomiciliary contacts, aged less than 15 years, from patients diagnosed with leprosy in the city of Rio Largo (AL) in the 2015 and 2016, and correlates them with clinical data obtained in dermatoneurological examinations, to estimate the real situation of the municipality in relation to leprosy. The determination of anti-PGL-1 serum and salivary antibodies was performed by solid phase enzymatic method (ELISA). The study included 68 contacts, with a mean age of 9.9 ± 2.9 years, 38 males and 30 females. Thirty-eight are contacts of multibacillary patients and 19 of paucibacillary patients, 22 are intra-domiciliary contacts and 44 are peridomiciliary contacts. Of the total, 17 had suspicious spots. In the year 2015, 66 contacts were evaluated. In both years of the study, anti-PGL-1 IgM levels were higher than IgA levels, which in turn were higher than IgG levels. In the year 2015, no correlation was observed between any analyzed isotypes. IgG levels were higher in contacts of multibacillary patients. Serum anti-PGL-1 IgM levels were higher in intradomiciliary contacts. In 2016, 44 contacts were evaluated. In relation to serum antibodies, anti-PGL-1 IgG and IgA showed a low positive correlation. Serum IgG levels were higher in paucibacillary contacts. There was no statistically significant difference between the intradomiciliary and peridomiciliary contacts. As for anti-PGL-1 salivary antibodies, IgM levels were higher in relation to IgA levels, and had a high positive correlation between them. However, they did not present statistical difference when evaluated as to the clinical form of the index case, the type of residence and the presence of suspicious spots. No statistical significance was also assessed when evaluating the corresponding serum antibodies. When compared between the years 2015 and 2016, serum IgM titers showed a high positive correlation and IgA was higher in the year 2015. It was observed that six contacts showed seropositivity for IgM and IgA, serum and / or salivary, simultaneously. Therefore, it is necessary for these contacts to be accompanied by the fact that they present a higher risk of progression to disease, when compared to contacts that did not present this type of change. Despite the limitations, the results suggest that serum anti-PGL-1, IgM, IgG and IgA, and salivary, IgM and IgA antibodies can be used in the investigation of contacts to assess the risk of progression to disease.